Filtro Cerâmico - uso como suporte do SrSnO3: para aplicação em catálise - Marinho, Rosa Maria de Medeiros (2011)
The present work consisted in the preparation of a ceramic filter, based on a reticulated porous ceramic, used as support for a catalyst with perovskite structure. The interest in these oxides is related to the easy modification of its catalytic properties, as a function of the adequate cation selection as well as to its high temperature stability. The ceramic filter was developed using an aqueous suspension containing natural raw materials (quartz, feldspar and kaolin) impregnated on a polymeric sponge. As catalyst, SrSnO3 was used in pure form or doped with 10 % of Ni (replacing Sr2+, Sn4+ or both), obtained by the polymeric precursor method. The filter was impregnated for 12 h in solution (SrSnO3), with 1, 3 and 5 baths, dried and sintered in O2 (350 oC) and air (700 oC) atmospheres, leading to the formation of the SrSnO3 film on the filter. Samples of pure and impregnated filters (SrSnO3:Ni) were characterized by Xray florescence, X-ray diffraction (XRD), Confocal Raman spectroscopy, infrared spectroscopy, scanning electronic microscopy and EDS (energy dispersive spectroscopy). XRD results for the pure filter presented quartz and mulite. For the supported filter, the presence of the perovskita phase was confirmed, being observed the crystallinity decrease with doping. SEM showed the non homogeneous formation of the film deposited on the filter. Broad bands in Raman and infrared spectra were not easily identified due to superposition of the filter and film peaks. In spite of this, it was possible to observe the Ni2+ presence in Sn4+ site in all samples. Ni2+ doping led to a short and long range disorder, confirmed by Raman and XRD. According to the photocatalytic tests, it was observed that the system filter:film, the so called catalytic filter, presented photocatalytic activity in the discoloration and degradation of the yellow remazol dye, while photolysis and the of the pure filter led only to the discoloration, with a higher half life.